Strategi Berkelanjutan dalam Pengelolaan Sampah Rumah Tangga di Kelurahan Mangunsari, Semarang - Nuni Widiarti; Budi Astuti; Sungkowo Sungkowo; Yuan Maylia Rosanti; Rojja Maysa Rohmah; Shinta Hilda; Syiva Zakia Aulia; Devitri Sulistyaningrum; Cepi Kurniawan (Jurnal Abdimas, 2024)
Kelurahan Mangunsari is located at Semarang city and emerges as a locale brimming with potential, yet grappling with the pervasive challenge of waste management, a predicament shared by many urban areas. This neighborhood faces the daunting task of dealing with both organic and inorganic waste, wherein the latter has seen some resolution through the establishment of a waste bank in RW 04. However, the management of organic household waste remains a critical issue. Addressing this, the Community Empowerment Team (PkM) from Universitas Negeri Semarang (Unnes) has embarked on a pioneering mission to imbue the local populace with the knowledge and skills necessary to transform waste into valuable resources, namely compost and ecoenzymes. This endeavor unfolds in three strategic phases: an educational campaign on waste management principles, hands-on training in compost and ecoenzyme production, and a rigorous monitoring phase to evaluate the program's efficacy. The initiative's results are commendable, marking a significant milestone in community-led waste management practices. Not only has it been successful in producing compost and ecoenzymes, but it has also fundamentally shifted the community's perception, recognizing the initiative as a transformative tool for enhancing household waste management. This case study not only underscores the potential of community empowerment in environmental stewardship but also serves as a replicable model for sustainable urban waste management solutions.